Pertumbuhan ikan Nila (Oreochromis niloticus) pada metode akuaponik dengan biofilter tanaman berbeda - Chintya Prameisella Hormati; Joppy D. Mudeng; Sammy N. J. Longdong; Novie P. L. Pangemanan; Ockstan J. Kalesaran; Sipriana S. Tumembouw (Universitas Sam Ratulangi, 2023)
The purpose of this study was to determine the type of vegetable plant as a biofilter in the aquaponics system that can trigger the growth of Nile tilapia (Oreochromis niloticus). This study was designed using a Complete Randomized Design with 4 treatments, namely treatment A biofilter pakchoy plant, treatment B biofilter lettuce plant, treatment C biofilter red amaranth plant and treatment D without plant biofilter (control), each with three replications. Fish were weighed at the beginning of the study and subsequently every week until the fourth week. Absolute growth and specific growth rate were evaluated while fish survival and water quality parameters were observed as supporting data. The results of the study found that pakchoy, lettuce, and red amaranth vegetable crops as biofilters in the aquaponics system had the same influence on the growth of tilapia (O. niloticus) but were significantly different from tilapia cultured without vegetable plant biofilters. Keywords: Nile tilapia, aquaponic, water quality, aquaculture, fish growth